Comparative Theoretical Investigation on Energetic Substituted Furazanyl Ethers - Liu, Ning; Shu, Yuanjie; Zeman, Svatopluk; Wang, Bozhou; Wang, Wenliang (My University, 2018)
Furazanyl ether has great potential to be an important candidate as a casting explosive and energetic plasticizer. The density functional theory (DFT) method was used to investigate the heats of formation (HOFs), molecular stability, detonation performance and melting point of a series of substituted furazanyl ethers at B3LYP/6-311G(d,p) level. The results show that the introduction of –N3 or –N(O)=N– groups significantly improves the HOFs values of the derivatives. The bond dissociation energies (BDEs) were analyzed, showing that the N–O bond in the furazan ring is the weakest for most compounds and the ring is vulnerable to cleavage in thermal decomposition. The calculation of density, detonation velocities and detonation pressures suggests that the substitution of –NF2, –CF(NO2)2, furoxan or –N(O)=N– group is an effective method for enhancing their detonation performance. The melting points were determined according to the variation of specific heat capacity, and good estimates were obtained in comparison with the available experimental data. Taking into account the detonation performance and melting point, four compounds are favoured for application in melt cast explosive or energetic plasticizers.
Srovnávací teoretické šetření energeticky substituovaných furazanyléterů
Keywords: furazanyl ethers; heats of formation; bond dissociation energy; detonation performance; melting point; furazanylové ethery; slučovací teplo; vazební disociační energie; výkon detonace; bod tání